Protocol for RETRO-TBI: A prospective cohort study of mild traumatic brain injury in older adults - Jennifer S. Albrecht; Odessa Addison; Neeraj Badjatia; Mary K. Bahr-Robertson; Lynn M. Grattan; Ann L. Gruber-Baldini; Rosemary Kozar; Jay Magaziner; Denise L. Orwig; Michelle Newman; Deborah Stevens; Emerson M. Wickwire; et al. (PLoS ONE, 2026)
Older adults experience the highest rates of traumatic brain injury (TBI) related hospitalizations and deaths of any age group, yet TBI remains understudied in this population. To improve understanding of recovery over the year following TBI among older adults, we designed the RETRO-TBI study. This manuscript reports the protocol for RETRO-TBI, a prospective cohort study of older adults (65 years and older) with mild TBI (mTBI) with planned enrollment of 250 participants. The study is designed to evaluate recovery across four key domains: physical function, cognitive function, psychological function, and sleep quality. Participants are followed for 12 months after injury, with in-home study visits conducted at approximately 2 weeks and 3, 6, and 12 months post-injury. Blood samples are collected at all visits. The specific aims are to: (1) identify trajectories of recovery in physical function and predictors of poorer physical recovery; (2) identify trajectories of recovery in cognitive function, psychological function, and sleep quality and predictors of poorer recovery in these domains; and (3) examine associations among recovery trajectories across domains. The RETRO-TBI study represents an important step in addressing the knowledge gap on recovery following TBI among older adults and is expected to result in identification of sub-groups of individuals more likely to have poor recovery, informing individualized treatment plans and development of future domain-based rehabilitation strategies. The study has several strengths including its focus on older adults, evaluation of recovery across four domains of function, and longitudinal assessments will permit evaluation of heterogeneity in recovery trajectories.